catena-Poly[[bis(nitrato-κ2O,O′)copper(II)]-μ-2,2′-(ethane-1,2-diyldithio)di-1,3,4-thiadiazole-κ2N4:N4′] - Hua-Ming Huang; Feng-Yang Ju; Jian-Ge Wang; Jian-Hua Qin (Acta Crystallographica Section E, 2009)
In the title compound, [Cu(NO3)2(C6H6N4S4)]n, the CuII atom, occupying a crystallographic inversion centre, is six-coordinated by two N atoms of two 2,2′-[1,2-ethanediylbis(thio)]bis[1,3,4-thiadiazole] ligands in trans positions, and four O atoms from two symmetry-related opposite nitrate anions, which are asymmetrically bonded, resulting in a strong distorted octahedral geometry of the central atom. The ethane group is equally disordered over two sites via another inversion centre. The bridging bidentate 2,2′-[1,2-ethanediylbis(thio)]bis[1,3,4-thiadiazole] ligands link the CuII centres into a one-dimensional chain. The chains are interconnected via intermolecular S...O interactions [3.044 (4) and 3.084 (5) Å] and weak C—H...O hydrogen bonds, generating a three-dimensional supramolecular structure.